Differentiated Thyroid Carcinomas: Therapeutic Follow-up and Hormone Replacement - Burak, Zeynep; Balcı, Tansel Ansal (Galenos Publishing House, 2026)
In patients diagnosed with differentiated thyroid cancer who have completed primary treatment, follow-up strategies are determined by evaluating the individual's risk of disease-related mortality and/or risk of disease recurrence. Currently, instead of applying a uniform standard approach to all patients, an individualized follow-up strategy is recommended. This approach, defined as dynamic risk stratification, is not a one-time assessment but an ongoing process that requires reassessment of risk at any point during patient follow-up. As part of the biochemical follow-up process, measuring serum thyroglobulin (Tg) and anti-thyroglobulin antibodies (anti-Tg Ab) is recommended, in addition to thyroid function tests. Among morphological follow-up methods, neck ultrasonography (US) is the most commonly used method. In cases where the US is inconclusive and in pathological subtypes with a high expectation of distant metastasis due to the nature of the disease, fluorine-18 fluorodeoxyglucose positron emission tomography-computed tomography and other cross-sectional imaging modalities are utilized. Although follow-up intervals vary depending on the initial risk of recurrence and the response to initial treatment, all patients should be monitored with serum Tg and anti-Tg Ab measurements and neck US at intervals of 6-18 months. During follow-up, thyroid stimulating hormone levels should be individualized based on the patient's risk of recurrence and therapeutic response; moreover, in elderly patients and those with comorbidities, particular caution should be exercised to avoid maintaining lifelong hormone replacement therapy at suppressive levels. Copyright © 2026 The Author. Published by Galenos Publishing House on behalf of Turkish Nuclear Medicine Society. This is an open access article under the Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0) License.
Diferansiye Tiroit Kanserlerine Yaklaşım: Tedavi Takibi ve Hormon Replasmanı
Keywords: differentiated thyroid carcinoma; Dynamic risk stratification; follow-up; hormone replacement